Analysis of Cargo Service Dynamics in East Asian Airports - LOW, Joyce Mei Wan (Institutional Knowledge at Singapore Management University, 2012)
This paper examines the effects of primary production and key economic factors on air cargo traffic between 1999 and 2005 in the East Asian airport industry through econometric and clustering analyses. This paper’s findings show that while the relative importance of physical capital to human capital has dramatically risen, adequate provisions and utilizations of physical facilities for landside operations appear to be a more significant driving force for an airport’s cargo traffic performances compared to those of airside operations. Even though cost savings are found to have regained their importance in the recent years, the degree of scale economies has fallen so sharply that airports can no longer rely on size for competitive edge. Nevertheless, there is still a close positive relationship between a nation’s economic development and the volume of cargo traffic at its airport.